Oil Spills and Fish Farming in the Niger Delta Region of Nigeria - Ipogah, David; F. A., Ikenga (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The ecosystem in the Niger Delta Region is highly diverse and supports numerous species of rich aquatic and terrestrial biodiversity which serves as the primary source of livelihood for the people. In order to address the oil pollution predicament this has made fishes to extinct and severe impact on human health. Three objectives and two hypotheses were raised to guide the study. Relevant and extant literatures were reviewed. This study is quantitative method and as such the questionnaire instruments was used to extract information from 45, 000 fishers in the core Niger Delta States. The demographic characteristics were analyzed by using simple percentage count and the chi-square statistical tool was used to test the hypotheses to determine the degree of freedom and significant relationship between variables. Based on the analysis, it was discovered that oil spills are usually due to continuous pipelines vandalism, gas flaring and oil drilling in the core Niger Delta States that destroy fishes and other aquatic elements in the environment. The study recommended among others that government and multinational oil companies should provide adequate measures to cushion the effect of pipelines vandalism, gas flaring and oil drilling in the Niger Delta. Government should also create synergy with non-government organizations to provide proactive measures for environmental sustainability in the Niger Delta Region.